Laser deposited coatings of Co‐Cr‐Mo onto Ti‐6Al‐4V and SS316L substrates for biomedical applications. Issue 7 (6th April 2013) - Wilson, J. Michael; Jones, Nolan; Jin, Li; Shin, Yung C.
<x xml:space="preserve">Abstract</x> Functionally gradient bio‐coating material was built by laser deposition. Co‐Cr‐Mo material was deposited on a Ti‐6Al‐4V substrate transitioning from 0% to 100%. Control over the cooling rate is shown to be a key to reduce the effects of thermal expansion differences of the materials. The microstructures and composition of the functionally gradient material (FGM) were characterized using an optical microscope, SEM, EDS, and XRD. EDS results showed a gradual transition to 50% Co‐Cr‐Mo and ∼100% Co‐Cr‐Mo on the top layer. XRD analysis showed the absence of a brittle intermetallic phase that forms between Titanium and Cobalt. As the amount of Co‐Cr‐Mo increased, the microhardness of the FGM samples significantly increased. A comparison was made between Co‐Cr‐Mo deposited on SS316L substrates as well as Ti‐6Al‐4V. The bonding strength of the coatings on both substrates was tested and found to meet the ASTM standard requirement. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 101B: 1124–1132, 2013.